ASSESSING BIOPHYSICAL AND SOCIOECONOMIC CONDITION FOR WATERSHED MANAGEMENT - Rajendra, P.S.; Gnanavelrajah, N. (Proceedings of the third GMSARN International Conference, 2008)
A study was carried out at Khlong Yai watershed of Thailand to assess soil erosion, and land suitability evaluation to examine the general land degradation status in terms of appropriateness of present land uses, and explore factors influencing farmers’ choices on land use selection. The study used both biophysical and socioeconomic data with standard available methodologies of soil erosion assessment and land evaluation. The data were collected from several sources including household survey. The study indicates that there is however enormous changes in land uses mostly due to commercial orientation the area has no serious soil erosion problem in general. The general choice of land use in the area is for tree crops due to commodity price for higher income, and other factors, such as traditional practice and tenure arrangement, nevertheless it is worth considering appropriate management practices in the area with tree crops as such cultivation practices diminishes ecological potential of land by diminishing soil fertility and biological diversity as well
Keywords: Soil Erosion; Land Evaluation; Diversity